(untitled) (Journal of the Bangladesh Agricultural University, 2025)
The growing threats of climate change are extremely acute for the coastal areas of Bangladesh. Understanding the use of adaptation strategies is crucial for overcoming these challenges and formulating effective adaptation policies. This study’s goals were to find out the socioeconomic characteristics of the respondents in coastal areas, to find out their use of adaptation strategies, and to find out the reasons of using and not using them. We collected data through surveys conducted in four villages within the Patharghata and Barguna Upazilas specifically targeting farmers who had implemented at least two adaptation strategies. The highest number of respondents moderately uses adaptation strategies in both areas. In terms of adoption rates, the salt-tolerant rice seeds and training were highest in both areas. However, barriers to adoption were also prevalent, with insufficient support and time constraints identified as significant challenges. The study highlights the importance of education and extension services in promoting adaptation strategies, alongside institutional support for overcoming barriers to adoption. To improve coastal Bangladeshi farmers’ resilience against climate change, educational programs, strengthened agricultural extension services, collaboration between government and non-governmental organizations, community engagement, and monitoring and evaluation systems are recommended. J Bangladesh Agril Univ 23(2): 157-165, 2025